Tuning the Schottky contacts at the graphene/WS2 interface by electric field. Issue 47 (6th June 2017) - Zhang, Fang; Li, Wei; Ma, Yaqiang; Tang, Yanan; Dai, Xianqi
Abstract : Evolution of Schottky barriers of Φ Bp and Φ Bn in graphene/WS2 heterostructures as a function of external electric field. Abstract : Using the first-principle calculations, we study the electronic structures of graphene/WS2 van der Waals (vdW) heterostructures by applying an external electric field ( E ext ) perpendicular to the heterobilayers. It is demonstrated that the intrinsic electronic properties of graphene and WS2 are quite well preserved due to the weak vdW contact. We find that n-type Schottky contacts with a significantly small Schottky barrier are formed at the graphene/WS2 interface and p-type (hole) doping in graphene occurs during the formation of graphene/WS2 heterostructures. Moreover, the E ext is effective to tune the Schottky contacts, which can transform the n-type into p-type and ohmic contact. Meanwhile, p-type (hole) doping in graphene is enhanced under negative E ext and a large positive E ext is required to achieve n-type (electron) doping in graphene. The E ext can control not only the amount of charge transfer but also the direction of charge transfer at the graphene/WS2 interface. The present study would open a new avenue for application of ultrathin graphene/WS2 heterostructures in future nano- and optoelectronics.